Mechanisms regulating myoblast fusion: A multilevel interplay. (August 2020) - Lehka, Lilya; Rędowicz, Maria Jolanta
Abstract: Myoblast fusion into myotubes is one of the crucial steps of skeletal muscle development (myogenesis). The fusion is preceded by specification of a myogenic lineage (mesodermal progenitors) differentiating into myoblasts and is followed by myofiber-type specification and neuromuscular junction formation. Similarly to other processes of myogenesis, the fusion requires a very precise spatial and temporal regulation occuring both during embryonic development as well as regeneration and repair of the muscle. A plethora of genes and their products is involved in regulation of myoblast fusion and a precise multilevel interplay between them is crucial for myogenic cells to fuse. In this review, we describe both cellular events taking place during myoblast fusion (migration, adhesion, elongation, cell-cell recognition, alignment, and fusion of myoblast membranes enabling formation of myotubes) as well as recent findings on mechanisms regulating this process. Also, we present muscle disorders in humans that have been associated with defects in genes involved in regulation of myoblast fusion.